The effects of certain personality and related variables on academic achievement - Morris, Margaret A. (1978)
This study investigated the possible effects of certain personality and related variables on performance in the 1977 General Certificate of Education (GCE) examinations of a group of Sixth Form students attending Jamaican high schools. Data were obtained from a sample of 163 students (70 boys, 93 girls) from five high schools in the Corporate Area of Kingston and St. Andrew. Results of the data analysis showed that: 1) personality variables affected achievement both directly and indirectly; 2) the best predictors of A'Level achievement were (a) Previous Examination Successes, Perception of Teachers, and Study Habits, for the total sample; (b) Previous Examination Successes, Early Educational Considerations, and Sociability for the male sample; and (c) Previous Examination Successes, Academic Orientation (negatively) and Perception of Teachers, for the female sample; and 3) Ascendancy (Low), Course Preference, and Authoritarianism (Low) emerged as the best predictors for the Science-based sample, and Perception of Teachers, Authoritarianism (Low), and Ascendancy for the Arts-based sample
Keywords: Academic achievement